The Greek versions of the TeamSTEPPS teamwork perceptions questionnaire and Minnesota satisfaction questionnaire "short form" - Ioanna Lakatamitou; Ekaterini Lambrinou; Martha Kyriakou; Lefkios Paikousis; Nicos Middleton (BMC, 2020)
Abstract Background Teamwork and job satisfaction are important among the multidisciplinary team who care patients with chronic illnesses such as heart failure (HF) patients. TeamSTEPPS teamwork perceptions questionnaire (T-TPQ) and Minnesota Satisfaction Questionnaire "short form" (MSQ-short) are both self-report questionnaires which examine multiple dimensions of perceptions of teamwork and job satisfaction within healthcare settings, respectively. The aim of the study was to examine the psychometric properties of the Greek versions of the TeamSTEPPS Teamwork perceptions questionnaire (Gr-T-TPQ) and Minnesota Satisfaction Questionnaire "short form" (Gr-MSQ-short). Methods A methodological study was contacted in order to assess the construct validity and reliability of the Gr-T-TPQ and Gr-MSQ-short. For that reason, 292 questionnaires were administrated to Greek-Cypriot health care professionals (HCPs). Confirmatory factor analysis (CFA) was conducted for the data collected with the GrT-TPQ and Exploratory factor analysis (EFA) and CFA were also conducted for the data collected with the GrMSQ-short questionnaire. Cronbach's a was calculated as well. Results CFA of the data collected with Gr-T-TPQ confirmed the initial scale structure with excellent fit indices (× 2 (df) 1124.75 (550), p < 0.0001, AGFI = 0.986, TLI = 0.994, CFI = 0.994, RMSEA = 0.06, 90%, C.I.[0.055-0.065]). Furthermore, all dimensions were found to be correlated (r = 0.65 to r = 0.88) and internal consistency was found adequate (Cronbach's α = 0.96). Subscales also, demonstrated high internal consistency (α = 0.87-0.95). CFA for the data collected with Gr-MSQ-short, did not confirm the initial scale's dimensions. In EFA items 1, 5, 6, 12 and 18 were eliminated from the analysis due to low communalities and multiple components loading. The oblimin rotation with two factors was explaining 58% of the variance. These two factors identified were Supervisor/Autonomy and Task Enrichment. Conclusions In general, the Gr-T-TPQ and Gr-MSQ-short are construct-valid instruments for measuring perceptions of teamwork and job satisfaction in Greek speaking HCPs' population.